Spoken Music in the Field of Spanish Experimental Music - García, Isaac Diego (Contemporary Music Review, 2021)
This article explores the phenomenon of spoken music in the field of contemporary Spanish experimental music. Spoken music is a hybrid form of artistic expression which draws on several disciplines such as sound poetry, performance art and experimental music relating to the development of the spoken voice. In Spain, spoken music does not appear in the field of avant-garde music-as it is still anchored in the expressionist tradition of the spoken voice-nor in the field of poetry, which is more concerned with the visual than the sonic, but rather in interdisciplinary spaces close to the thinking of John Cage and the artistic universe of Fluxus. In 1966, in the setting of the group Zaj, Ramon Barce (1928-2008) created one of the paradigmatic pieces of spoken music:Coral hablado('Spoken choral'). Subsequently, various groups emerged, dedicated to creating and performing works of this nature. Flatus Vocis Trio is especially noteworthy among these groups as it is probably the most important group in the area of spoken music in Spain. Using the work of this group, this study reflects on various aspects of its artistic essence, such as the aesthetic and communicative dimension of the spoken voice, its difficult relationship with the semantic function and its distance from the principal trends in sound poetry, among others.
Keywords: experimental music; flatus vocis trio; sound art; spoken music; sound poetry; zaj; WOS